Carbonaceous Components in PM2.5 and PM0.1 with Online Measurements of Gaseous and Particulate Pollutants: Implication of Thermal-Optical Derived EC2 Fraction as a Component of Ultrafine Particles in the Roadside Environment - Kim, Kyung Hwan; Woo, Sung Ho; Lee, Seung-Bok; Bae, Gwi-Nam; Sekiguchi, Kazuhiko; Kobayashi, Ryota; Kamiyama, Motomi (TAIWAN ASSOC AEROSOL RES-TAAR, 2016)
An investigation of the carbonaceous components of PM2.5 (D-p < 2.5 mu m) and PM0.1 (D-p < 0.1 mu m) in conjunction with online measurements of gaseous and particulate pollutants, which are dominated by motor vehicle emissions, was undertaken over 15 consecutive days in a field sampling campaign at a roadside and reference site for daytime (06: 00 to 17: 30) and nighttime (18: 00 to 05: 30) conditions. The results indicated that traffic-related air pollutants strongly influenced pollution levels in the sampling area, especially during the nighttime, although the concentrations were lower than during the daytime. Water-soluble organic carbon/organic carbon (WSOC/OC) ratios in PM0.1 were 0.60 +/- 0.11 and 0.63 +/- 0.16 at the roadside and reference sites, respectively, while the corresponding ratios in PM2.5 were found to be 0.60 +/- 0.11 and 0.63 +/- 0.14. These results demonstrated the relatively high contribution of WSOC in the study area compared to in previous reports. It was observed that elemental carbon (EC) in PM0.1 are emitted approximately by a factor of 0.1 in comparison with those observed for EC in PM2.5 when considering the slopes of the linear relationship with particle-bound PAHs and NOx, while OC displayed no such relationship. Our measurements indicate that a significant portion of the OC in PM0.1 is not directly co-emitted with EC from motor vehicles but is readily adsorbed or condensed onto the existing EC fractions through condensation. The relationship between the EC2 fraction and the particle number concentration indicates that the EC2 fraction is the primary chemical component of traffic related ultrafine particles in terms of particle number concentration.
Keywords: SECONDARY ORGANIC AEROSOL; ELEMENTAL CARBON; FINE PARTICLES; LOS-ANGELES; THERMAL/OPTICAL REFLECTANCE; CHEMICAL CHARACTERISTICS; SOURCE IDENTIFICATION; SAMPLING ARTIFACTS; ATLANTA AEROSOL; MATTER